Dance Learning Model in the Education of the Independent Curriculum - Adzan, Nabilla Kurnia; Setiawan, Afrizal Yudha; Anastasya, Putri Novia (Jurnal Seni Tari, 2024)
Until 2024, at least four curricula have been used as a reference for implementing learning in schools. Currently, the curriculum used is the independent curriculum. This curriculum covers learning from early childhood to the tertiary level. All lessons at school are regulated in the independent curriculum, including dance. The word independence in the curriculum invites teachers and students to freely choose materials, learning models, methods, media, and evaluation techniques in implementing learning. It intersects with the educational dance learning model. This research looks at how dance learning in the independent curriculum is implemented with an educational dance perspective containing two main things, namely creative and expressive dance. This research used a qualitative descriptive method using observation, interview, and documentation data collection techniques. This research presents a description of dance learning at the high school level. The research results show that several schools in Lampung have implemented learning as stated in the independent curriculum before this curriculum existed in Indonesia. This research describes how this learning takes place.